Nanopore long-read RNA-seq and absolute quantification delineate transcription dynamics in early embryo development of an insect pest - Bayega, Anthony; Oikonomopoulos, Spyros; Gregoriou, Maria-Eleni; Tsoumani, Konstantina T.; Giakountis, Antonis; Wang, Yu Chang; Mathiopoulos, Kostas D.; Ragoussis, Jiannis (Scientific reports, 2021)
The olive fruit fly, Bactrocera oleae , is the most important pest for the olive fruit but lacks adequate transcriptomic characterization that could aid in molecular control approaches. We apply nanopore long-read RNA-seq with internal RNA standards allowing absolute transcript quantification to analyze transcription dynamics during early embryo development for the first time in this organism. Sequencing on the MinION platform generated over 31 million reads. Over 50% of the expressed genes had at least one read covering its entire length validating our full-length approach. We generated a de novo transcriptome assembly and identified 1768 new genes and a total of 79,810 isoforms; a fourfold increase in transcriptome diversity compared to the current NCBI predicted transcriptome. Absolute transcript quantification per embryo allowed an insight into the dramatic re-organization of maternal transcripts. We further identified Zelda as a possible regulator of early zygotic genome activation in B. oleae and provide further insights into the maternal-to-zygotic transition. These data show the utility of long-read RNA in improving characterization of non-model organisms that lack a fully annotated genome, provide potential targets for sterile insect technic approaches, and provide the first insight into the transcriptome landscape of the developing olive fruit fly embryo.